Recent Advances in the Deposition of Diamond Coatings on Co-Cemented Tungsten Carbides. (11th October 2012) - Polini, R.; Barletta, M.; Rubino, G.; Vesco, S.
Abstract : Co-cemented tungsten carbides, namely, hard metals are largely used to manufacture high wear resistant components in several manufacturing segments. Coating hard metals with superhard materials like diamond is of utmost interest as it can further extend their useful lifespan. The deposition of diamond coatings onto WC-Co can be extremely complicated as a result of poor adhesion. This can be essentially ascribed to (i) the mismatch in thermal expansion coefficients between diamond and WC-Co, at the typical high temperatures inside the chemical vapour deposition (CVD) chamber, generates large residual stresses at the interface; (ii) the role of surface Co inside the WC-Co matrix during diamond CVD, which promotes carbon dissolution and diffusion. The present investigation reviews the techniques by which Co-cemented tungsten carbides can be treated to make them prone to receive diamond coatings by CVD. Further, it proposes interesting ecofriendly and sustainable alternatives to further improve the diamond deposition process as well as the overall performance of the coated hard metals.